Development of robust platform for biomaterials applications assembly with AFM mesurement - Chin, Hokyun (Nanyang Technological University, 2020)
Cellular membrane host a variety of crucial biological activities such as trafficking molecules in and out of cells, protecting the cell from external assaults, maintain homeostasis, segregate the internal composition and provide specificity. Improved capabilities to study the lipid membrane properties and to quantify their characteristics is an important scientific goal that would enable the better understanding of the very origins of life to the development of targeted therapeutics. To these artificial membrane organizations spanning planar to vesicular configurations have been used as a simplified mimic model of biological membranes. There is an ever-growing interest in generating planar bilayer as they are relatively easy to prepare, are stable and can provide a versatile platform through patterning. More importantly, a variety of surface sensitive techniques such as FRAP, QCM/QCM-D, SPR, and AFM can be used to extract useful information about their biophysical properties. In particular, the Atomic Force Microscopy (AFM) techniques have shown great promise in the successful characterization of membrane topography by offering high-resolution with non-contact imaging capabilities in the liquid environment that are biologically more relevant. Despite this, it remains a challenge in to determine useful parameters in a fluid condition using AFM. One of the main drawbacks comes from the lack of better sealing systems that would reduce not only the volume of liquid but also create more uniform flow, which is essential for bilayer formation. Moreover, there is often limited solvent exchange through the conventional AFM sample chambers. Exchange of solvent would enable more versatility in creating the custom environment for bilayer studies using AFM. To address these drawbacks, my proposed scheme of the Ph.D. program includes developing more versatile biophysical tools for studies using AFM to explore properties of biological materials. As a first step, I have designed fluidic chamber for AFM that addresses the drawbacks mentioned above of the conventional liquid sample chamber. The newly designed sample chamber is modular, uses the minimal sample solvent and enables the use of a wide variety of lipids reagents while measuring biophysical properties of the lipid bilayer. As a proof of concept, I investigated the morphological and mechanical properties of the supported lipid bilayer made from varying lipids. Using the mixed-lipids platform for planar bilayer formation is known to form domains usually, in case of they have a different transition temperature. The new sample chamber, therefore, shows promising applications in the field of complex bilayer studies in a variety of context. As a final remark, a brief discussion on the ongoing work on the Extracellular Matrix (ECM) membrane studies combining with the AFM application is outlined.